Pengetahuan dan Dukungan Keluarga terhadap Kepatuhan Penggunaan OAT di Dua Puskesmas di Kabupaten Lombok Utara - Rizka Novia Atmadani; Utari Dita Fitriana; Mutiara Titani (Publikasi oleh Fakultas Kedokteran Universitas Islam Malang, 2022)
Abstract. Tuberculosis (TB) is a disease that is transmitted by the bacterium Mycobacterium tuberculosis. Adherence in pulmonary TB treatment is important so that patients can recovery. According to Lawrenve Green’s theory, factors that influence patient compliance behavior in taking medication are predisposing, enabling, and rein- forcing factors. Research Methods: The research design used is des- criptive correlative using a cross sectional approach. This research was conducted in August 2022, the samples were 40 patients with pulmo- nary TB who were treated at the Gangga Health Care and Tanjung Health Care, North Lombok Regency with accidental sampling tech- nique. The research instrument used in this study was a questionnaire and analyzed by Chi-Square test using software SPPS version 24.The results of the validity and reliability tests have met the requirements Result and Discussion: Patients who have good knowledge of 95.0%, 5.0% good knowledge, and family support of 87.5 % good knowledge, 12.5% poor knowledge. Patients with good knowledge were found to have 85.0% adherence to the use of OAT. The results from bivariate analysis, the level of knowledge P-value = 0.019 < α = 0.05, and family support P-value = 0.018 < α = 0.05 Conclusion There is relationship between the level of knowledge with Tuberculosis patient adherence in taking OAT, and there is relationship between the level of family support with Tuberculosis patient adherence in taking OAT at the Gangga Health Center and Tanjung Health Center, North Lombok Regency.